Short-term prediction of coronary heart disease mortality in the Czech Republic based on data from 1968-2014 - Reissigová, Jindra; Zvolský, Miroslav (Central European Journal of Public Health, 2018)
OBJECTIVES: The aim was to explore the patterns of the coronary heart disease (CHD) mortality rates over the past almost 50 years (1968-2014) in the Czech Republic, and to predict the mortality rates in 2015-2019. METHODS: The number of deaths from CHD and the population size were stratified by sex and age. The mortality rates were age-standardized to European population. Their values in 2015-2019 were estimated using the joinpoint log-linear regression, local log-linear regression and negative binomial log-linear regression, separately for males and females. RESULTS: A positive change in the trend of the age-standardized mortality rates from CHD was detected after the collapse of communism in 1989. In 1991-2000, the mortality trend was sharply downward, with an annual percent change of -5.8 % for males and -5.2 % for females. In 2000-2014, the decreasing trend was not so sharp (-1.3 % for males and -0.7% for females), yet it should continue in 2015-2019. The crude mortality rates for females are slightly higher than those for males since 2007, however, they are increasing for both sexes. The mortality rates are rising mainly in the age group of 85+ years (in 2014, 25.4% of CHD deaths of males and 54.4% of females occurred at the age of 85+ years). CONCLUSIONS: The age-standardized mortality rates are predicted to decrease in 2015-2019, but the crude mortality rates should increase due to increase in average life expectancy. The burden of deaths is moving to the age group of 85 years and older, mainly in females. A total of 26,039 CHD deaths were registered in the Czech Republic in 2014, and 29,653 are predicted for 2019, if the current trends continue.
Keywords: lidé středního věku; Age Distribution; věkové rozložení; Male; dospělí; Coronary Disease; lidé; senioři nad 80 let; senioři; Aged; Czech Republic; Česká republika; Risk Factors; ženské pohlaví; Aged, 80 and over; Adult; koronární nemoc; mužské pohlaví; rizikové faktory; Middle Aged; Humans; Female